Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
Step-by-step explanation:
Let AC = x
AB - AC = 4 cm
AB = 4 +x ----------------(I)
Pythagorean theorem
AB² + AC² =BC²
(4 + x)² + x² = 9²
Use the identity (a + b)² = a² + 2ab + b² where a = 4 & b = x
4² +2*4*x +x² + x²= 81
16 + 8x + 2x² = 81
2x² + 8x + 16 - 81 = 0
2x² + 8x - 65= 0
a = 2 ; b = 8 ; c = -65
D = b² - 4ac
= 8² - 4*2*(-65)
= 64 + 520
D = 584
√D = √584 = 24.16
[tex]x=\frac{-b+\sqrt{D}}{2a} \ or \ x =\frac{-b-\sqrt{D}}{2a}\\\\x= \frac{-8+24.16}{2*2} \ or \ x = \frac{-8-24.6}{2*2}[/tex] {Ignore this as it is negative.}
x = 16.16/4
x = 4.04
AC = 4.04 Cm
AB = 4 + 4.04 = 8.04 cm
Area of triangle ABC = [tex]\frac{1}{2}* base * height[/tex]
[tex]=\frac{1}{2}*4.04 *8.04\\\\= 2.02 * 8.04[/tex]
= 16.24 sq.cm
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.